Radial Mononeuropathies - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1996)
Sixteen cases of radial mononeuropathy, presenting with wristdrop and seen in the EMG laboratory at Children's Hospital, Boston, during 16 years, 1979-95, were analysed.